All of Us: A National Effort to Improve Health. Issue 4 (2nd October 2022) - Epstein, Helen-Ann Brown
Abstract: In healthcare one size does not fit all. If one was ill, wouldn't it be great for them to receive medicines made precisely for them? It is the aim of the All of Us campaign to do just that. Overtime, All of Us hopes to collect one million DNA samples and other valuable health information from a diverse group of people in the United States by about 2024. Studying these samples will reveal to researchers likenesses and differences across the samples to improve health by creating precise personal remedies and treatments. This column introduces the All of Us campaign, illustrates the research efforts using the All of Us data and closes with where one can contribute to this monumental effort.